An approach of dynamic filter for weather environment dependent on time. - Al-Zyadat, Wa'el Jum'ah; Atan, Rodziah (2010)
In general dynamic filter has difficulty to execute the process because the Input /Output rapid change and its link-time directly almost work is synchronized within received data, the effectiveness for the results its and evaluations for all functions to process compatible usability, the structure designed for approach is Full Life Cycle Object-Oriented Testing (FLOOT) which aims the domain for weather its special environment which means high data sets is needed to support for end-user to predict the results in addition FLOOT give validity forward and backward processes and able to correct any error if discovered. Through experiments, we show our approach improves the performance of filtering information in two types of recognizes errors systems adopting the re-process data and visualization, respectively. In this paper will provide approach to resolve impact environment to data stream and enhancement filtering process interaction.